2022
DOI: 10.3389/fphar.2022.859951
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Intraocular Biomolecules in Retinal Vein Occlusion: Toward Potential Biomarkers for Companion Diagnostics

Abstract: Retinal vein occlusion (RVO) is one of the most common retinal vascular diseases. The pathogenesis of RVO is multifactorial and involves a complex interplay among a variety of vascular and inflammatory mediators. Many cytokines, chemokines, growth factors, and cell adhesion molecules have been reported to be implicated. Treatments for RVO are directed at the management of underlying risk factors and vision-threatening complications, including macula edema (ME) and neovascularization. Intravitreal anti-VEGF age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 142 publications
(300 reference statements)
0
7
0
Order By: Relevance
“…EC Casp9 regulates an increase in inflammatory cytokines one day P-RVO After we found that EC Casp9 promoted a decline in vision function, we sought to evaluate the EC Casp9 downstream signaling pathway which mediates loss of vision. Inflammatory cytokines are known to be a main contributor of neovascularization, and correlate with hypoxic-ischemic injury and retinal edema [27], and are implicated in RVO pathology (summarized in the recent review [40]). Our previous work revealed that the peak of retinal edema in the EC Casp9 mouse line is two days P-RVO which coincided with a significant decrease in hyperreflective foci (HRF) (a clinical biomarker of inflammation [41][42][43]) [10].…”
Section: Resultsmentioning
confidence: 99%
“…EC Casp9 regulates an increase in inflammatory cytokines one day P-RVO After we found that EC Casp9 promoted a decline in vision function, we sought to evaluate the EC Casp9 downstream signaling pathway which mediates loss of vision. Inflammatory cytokines are known to be a main contributor of neovascularization, and correlate with hypoxic-ischemic injury and retinal edema [27], and are implicated in RVO pathology (summarized in the recent review [40]). Our previous work revealed that the peak of retinal edema in the EC Casp9 mouse line is two days P-RVO which coincided with a significant decrease in hyperreflective foci (HRF) (a clinical biomarker of inflammation [41][42][43]) [10].…”
Section: Resultsmentioning
confidence: 99%
“…In an earlier study, we showed a significant correlation between levels of MCP-1 and IL-8 in aqueous humor in BRVO [ 18 ]. In an in vivo experiment in rats, retinal vein occlusion increased the rolling and venous wall adhesion of leukocytes, markedly decreasing blood flow [ 40 ], so in BRVO with macular edema, this process may be responsible for decreasing RFV [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is indirect evidence from human 16 and direct evidence from animal 14,17 studies that support our idea; for example, in patients with pre-existing higher EPO levels, the efficacy of anti-VEGF treatment was lower than that of patients with lower EPO levels. 18 In addition, in an animal model of musculocutaneous tissue ischemia, flaps treated with EPO and bevacizumab did not show any change in tissue necrosis when compared with animals receiving EPO only, 19 supporting a possible counteraction between EPO and anti-VEGF agents. It might be argued that the interaction between locally administered exogenous anti-VEGF and endogenous intravitreal EPO and/or VEGF levels is complex.…”
Section: Evaluation Of Hypothesismentioning
confidence: 91%